Analytical Study on The Intensity of Surface Urban Heat Island (SUHI) in Kaduna State - Onibaba, Paul; Otokiti, Kolade Victor; Ademola, Oluwabukola Grace; Akanle, Temitope Mercy (CSID Journal of Infrastructure Development, 2024)
Urbanization and climate change are significant drivers of rising Land Surface Temperature (LST) and the formation of Urban Heat Islands (UHIs), which have emerged as pressing environmental challenges in recent decades. This study examines the relationship between Land Use/Cover (LU/C) indices and LST in Kaduna, Nigeria, using multi-temporal Landsat imagery spanning five periods from 2001 to 2021. LST values were derived from the Landsat thermal bands, while LU/C dynamics were identified using the Maximum Likelihood Classifier algorithm. LU/C indices—including the Normalized Difference Vegetation Index (NDVI), Normalized Difference Built-up Index (NDBI), Modified Normalized Difference Water Index (MNDWI), and Soil-Adjusted Vegetation Index (SAVI)—were generated to evaluate their correlation with LST. The results highlight a substantial increase in built-up areas over the 20-year period, accompanied by rising LST values, particularly over bare land and built-up regions, while water bodies exhibited the lowest LST values. Among the LU/C indices, NDBI showed the strongest positive correlation with LST, emphasizing the influence of urban expansion on surface thermal dynamics. The study underscores the critical need for sustainable urban planning and holistic design strategies to mitigate rising LST and SUHI effects in rapidly urbanizing regions like Kaduna.